Development of Rhabdomyolysis in the Long-term Period of Previous New Coronavirus Infection COVID-19 (Clinical Case Report) - G. A. Berdnikov; N. Y. Kudryashova; E. V. Migunova; S. I. Rey; E. V. Gurok; Kh. K. Abdulamitov; E. V. Klychnikova; O. G. Maklyayeva (Неотложная медицинская помощь, 2021)
Relevance. Rhabdomyolysis is one of the complications of the new coronavirus infection COVID-19, which may cause acute kidney injury (AKI). The reason for the development of rhabdomyolysis in our observation in a patient after suffering COVID-19 in the long-term period was an increased muscle load.Aim of study. Presentation of a case of rhabdomyolysis with AKI in a patient after COVID-19 in the long-term period.Material and methods. In clinical observation, a 25-year-old patient L. is presented, who was being treated in the Department for the Treatment of Acute Endotoxicosis of the N.V. Sklifosovsky Research Institute for Emergency Medicine. In 2020, he developed COVID-19, complicated by rhabdomyolysis and AKI in the long term period.Results. Examination revealed an increase in creatinine phosphokinase (CPK) — 106,000.0 U/L, alanine aminotransferase (ALT) — 553.0 U/L, aspartate aminotransferase (AST) — 1582.0 U/L, lactate dehydrogenase (LDH) — 2809.0 U/L, levels of serum creatinine 164 μmol/L and myoglobin — 201 ng/ml. Virological research: IgM — 0.27 units per ml; IgG — 7.28 units per ml. 3 Three-phase scintigraphy with 99mTc-pyrfotech revealed signs of necrotic changes in the muscles of the upper half of the back, muscles of the chest (mainly on the right), muscles of the shoulder and upper half of the forearm on both sides. Kidneys: decreased perfusion of the right kidney (relative to the left), moderate slowdown of urodynamics at the level of the calyx-pelvis complex on both sides.Conclusions. The reason for the development of rhabdomyolysis in the long-term period in the patient after suffering from COVID-19 was an increased muscle load. Targeted research and medical history can help identify signs of rhabdomyolysis. The use of the radionuclide diagnostic method makes it possible to identify areas of soft tissue damage with a one-step assessment of renal function in rhabdomyolysis in the acute period of the disease, as well as to evaluate the effectiveness of treatment with dynamic observation. When rhabdomyolysis is confirmed, it is necessary to carry out detoxification and infusion therapy, to monitor renal function in order to detect acute kidney injury, and in case of deterioration of renal function and intoxication, renal replacement therapy is indicated.